Просто подставлять в формулу...
x^2-4x+3=0\\a=1,b=-4,c=3\\D=b^2-4ac\\D=(-4)^2-4\cdot 1\cdot 3=16-12=4\\x=\frac{-b\pm \sqrt{D}}{2a}=\frac{4\pm 2}{2}=\left \{ 1,3 \right \}
Автор:
cesáreofokv\displaystyle\bf\\x^{2} -4x+3=0\\\\a=1 \ \ ; \ \ b=-4 \ \ ; \ \ c=3\\\\D=b^{2}-4ac\\\\D=(-4)^{2} -4\cdot 1\cdot 3=16-12=4\\\\\\x_{1} =\frac{-b-\sqrt{D} }{2a} =\frac{4-\sqrt{4} }{2\cdot 1} =\frac{4-2}{2} =\frac{2}{2} =1\\\\\\x_{2} =\frac{-b+\sqrt{D} }{2a} =\frac{4+\sqrt{4} }{2\cdot 1} =\frac{4+2}{2} =\frac{6}{2} =3\\\\\\Otvet \ : \ 1 \ ; \ 3
Автор:
alejandroleeДобавить свой ответ
Предмет:
Английский языкАвтор:
giselaОтветов:
Смотреть
Предмет:
Английский языкАвтор:
prancerОтветов:
Смотреть
Предмет:
МатематикаАвтор:
aguirreОтветов:
Смотреть